Baxter Family : The Baxters - A Prequel - Kingsbury, Karen (New York : Atria Books, 2022)
On Kari Baxter's wedding day, a building storm brings conflict and doubt to the family until a moment of danger reveals important truths, which could bring them back together or tear them apart.
Keywords: Weddings -- Fiction; Storms -- Fiction; Families -- Fiction; Indiana -- Fiction; Christian fiction; Romance fiction; Novels